2019
DOI: 10.1088/2399-6528/ab18de
|View full text |Cite
|
Sign up to set email alerts
|

Comments on the fractal energy spectrum of honeycomb lattice with defects

Abstract: We study the fractality of the energy spectrum of honeycomb lattice with various defects or impurities under a perpendicular magnetic field. Using a tight-binding Hamiltonian including interactions with the nearest neighbors, we investigate its energy spectrum for different choices of point defects or impurities. First, we fix a unit cell consisting of 8 lattice points and survey the energy eigenvalues in the presence of up to 2 point defects. Then it turns out that the existence of the fractal energy structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…For further research directions, it will be meaningful to consider the theory with impurities or defects, by which we can address the problems under more realistic conditions. In our recent study [49,50], we showed that the fractal scaling nature of the localized length of the Bloch states localizing around a defect. Studying the localized length can be a powerful method to investigate the fractal nature of the Hofstadter butterfly as well as the energy spectrum.…”
Section: Conclusion and Discussionmentioning
confidence: 93%
“…For further research directions, it will be meaningful to consider the theory with impurities or defects, by which we can address the problems under more realistic conditions. In our recent study [49,50], we showed that the fractal scaling nature of the localized length of the Bloch states localizing around a defect. Studying the localized length can be a powerful method to investigate the fractal nature of the Hofstadter butterfly as well as the energy spectrum.…”
Section: Conclusion and Discussionmentioning
confidence: 93%
“…For further research directions, it will be meaningful to consider the theory with impurities or defects, by which we can address the problems under more realistic conditions. In our recent study [46,47], we showed that the fractal scaling nature of the localized length of the Bloch states localizing around a defect. Studying the localized length can be a powerful method to investigate the fractal nature of the Hofstadter butterfly as well as the energy spectrum.…”
Section: Conclusion and Discussionmentioning
confidence: 93%
“…There are many possible further research directions. For example, it would be a good exercise to simulate dynamics of systems with defects [37]. Moreover in principle, such dynamics can be simulated with a general Ising model with XX interactions.…”
Section: Discussionmentioning
confidence: 99%